Preventive podriatic medicine: painful back syndrome in the podiatrist - Gentil García, Isabel (Revista Internacional de Ciencias Podológicas, 2008)
The podiatrist are included into a professionals affected by Painful Back Syndrom. The most activities are doing with the back tilt ahead because the clinician need to get visual and precise information in order to perform meticulous techniques. The principal risk factor of Painful Back Syndrom is the mal position at work that produces muscular fatigue, decrease of miofibers energy and liberation of anaerobic metabolits that produce pain and muscular contraction. For all that reasons it is important knowing and practising preventive measures.